Analysis of the Influence of Work Culture and Work Environment on Employee Turnover Intention PT. ABC President Indonesia - Astuti, Widia; Yanuarso, Bambang Purnomo; Sunaryo, M. Yusuf (Formosa Journal of Science and Technology, 2025)
The purpose of this research is to analyze how much influence between work culture and work environment on employees turnover intention at PT ABC President Indonesia, both partially and simultaneously. The used research method is a quantitative method. Data collection techniques used were observation, interviews and distributing questionnaires. Data analysis methods used were normality test, multicollinearity test, heteroscedasticity test, F test, T test, coefficient test of determination and multiple linear regression. Population 150 people with sample used was 60 people according to calculations using the Slovin formula with a tolerance error of 0,1 or 10%. Based on the results obtained that the work culture and work environment at PT ABC President Indonesia (ABCPI) could be said to be unfavorable and has much affect on turnover intention both partially and simultaneously. This is evidenced by the results of the T count 3,780 > t table 1,6720 for the influence of work culture on turnover intention, the result of T count 1,952 > t table 1,6720 for the influence of the work environment on turnover intention, and the F test 16,236 > F table 3,16. Also based on the results of coefficient test of determination, the value of R Square is 0,363 which means that work culture and work environment affected of turnover intention by 36.3%.